Pengaruh Profitabilitas, Solvabilitas, Likuiditas Dan Size Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2016-2021 - Maharani Jaya Wardhani; Sunarto Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research was prepared with the aim of testing and analyzing the effect of Profitability, Solvency, Liquidity and Size on stock prices in Manufacturing Companies in the consumer goods sector that have been listed on the Indonesia Stock Exchange (IDX) in the period 2016 to 2021. The method used by researchers is purposive sampling with the criteria for company data during the period 2016 to 2021, has positive profits, has never been suspended. The sample used consists of 191 data on consumer goods industry companies listed on the Indonesia Stock Exchange between 2016 and 2021. The Multiple Linear Analysis method is used by researchers in analyzing data and processed using SPSS 25. The results of this study indicate that, profitability (X1), solvency (X2) and liquidity (X3) cannot affect stock prices (Y). Meanwhile, size has a negative influence on stock prices. Keywords: Profitability, Solvency, Liquidity, Size, Stock Price